Prevalence of Candida spp. during radiographic examination in Diabetes mellitus patients - Flávia Cristina Volpato; Juliana Rico Pires; Isis do Rosário da Costa Martinez; Silvana Regina Perez Orrico; Marciano Pires da Costa; Denise Madalena Palomari Spolidório; Andréa Gonçalves
INTRODUCTION: It is suggested that individuals with diabetes are more susceptible to Candida infections than healthy people, especially if periodontal infection is associated. OBJECTIVE: This study evaluated the prevalence of colonization by Candida spp. during radiographic examination in diabetic and non-diabetic patients. MATERIAL AND METHODS: Twenty-six patients with type 2 diabetes mellitus and 20 patients without diabetes mellitus, presenting chronic periodontitis and presence of Candida spp. in saliva were evaluated. During radiographic examination, samples of saliva were collected from: oral mucosa, conventional radiographic periapical film, digital x-ray sensor (CDR), and bite block of the receptor-positioning device. Colony forming units (cfu/mL) and identification of Candida yeasts were assessed. RESULT: Oral mucosa from both groups showed the highest colonization with Candida spp. if compared with others surfaces collected (p < 0.05). In diabetic patients, the mucosa of the upper left regions showed higher levels of colonization. In non-diabetic patients, the upper right molar region showed the highest level of colonization during the examination of the receptor-positioning device, the sensor and the non-sensitive film. Candida spp. levels in saliva were similar between diabetics (mean = 3.0 × 10(6)) and non-diabetics (mean = 3.8 × 10(6)). CONCLUSION: No difference in Candida spp. colonization (cfu/mL) in diabetics and non-diabetic patients was observed for the five collected surfaces and the simulated radiographic region. Candida albicans was the prevalent species of Candida spp. found on all the samples.